Altered immunoreactivity of ErbB4, a causative gene product for ALS19, in the spinal cord of patients with sporadic ALS. Issue 4 (24th May 2019) - Takahashi, Yuji; Uchino, Akiko; Shioya, Ayako; Sano, Terunori; Matsumoto, Chihiro; Numata‐Uematsu, Yurika; Nagano, Seiichi; Araki, Toshiyuki; Murayama, Shigeo; Saito, Yuko
Abstract : ErbB4 is the protein implicated in familial amyotrophic lateral sclerosis (ALS), designated as ALS19. ErbB4 is a receptor tyrosine kinase activated by its ligands, neuregulins (NRG), and plays an essential role in the function and viability of motor neurons. Mutations in the ALS19 gene lead to the reduced autophosphorylation capacity of the ErbB4 protein upon stimulation with NRG‐1, suggesting that the disruption of the NRG–ErbB4 pathway causes motor neuron degeneration. We used immunohistochemistry to study ErbB4 in the spinal cord of patients with sporadic ALS (SALS) to test the hypothesis that ErbB4 may be involved in the pathogenesis of SALS. ErbB4 was specifically immunoreactive in the cytoplasm of motor neurons in the anterior horns of the spinal cord. In patients with SALS, some of the motor neurons lost immunoreactivity with ErbB4, with the proportion of motor neurons with a loss of immunoreactivity correlated with the severity of motor neuron loss. The subcellular localization was altered, demonstrating nucleolar or nuclear localization, threads/dots and spheroids. The ectopic glial immunoreactivity was observed, mainly in the oligodendrocytes of the lateral columns and anterior horns. The reduction in the ErbB4 immunoreactivity was significantly correlated with the cytoplasmic mislocalization of transactivation response DNA‐binding protein 43 kDa (TDP‐43) in the motor neurons. No alteration in immunoreactivity was observed in the motor neurons of mice carrying atransgene for mutant form of the superoxide dismutase 1 gene ( SOD1 ). This study provided compelling evidence that ErbB4 is also involved in the pathophysiology of SALS, and that the disruption of the NRG–ErbB4 pathway may underlie the TDP‐43‐dependent motor neuron degeneration in ALS.